Volatility Analysis of the Indonesia Sharia Stock Index (ISSI) Technology Sector Period 2019 – 2023 - Bimantoro, Surya Ageng; Yasin, Ach (Formosa Journal of Applied Sciences, 2025)
The Indonesian capital market faced significant challenges during the COVID-19 pandemic, which caused stock price volatility across various sectors, both in the conventional and sharia capital markets, particularly in the technology sector (ISSI). This study uses a descriptive quantitative approach, employing purposive sampling to analyze secondary data obtained from Yahoo Finance to explore technology stocks consistently listed from 2019 to 2023 on the ISSI, focusing on daily closing prices, volatility, and utilizing ARCH/GARCH modeling in EViews 10. Descriptive analysis reveals significant stock price fluctuations. The research results indicate that there are variations in the volatility levels of technology sector stocks on the Indonesia Sharia Stock Index from January 1, 2019, to December 29, 2023. Stocks ranked by volatility from highest to lowest are MCAS, MLPT, KIOS, NFCX, and DIVA, with volatility analysis using the GARCH model.